Correlation among mutans streptococci counts, dental caries, and IgA to Streptococcus mutans in saliva Correlação entre contagens de estreptococos do grupo mutans, cárie dentária e IgA anti-Streptococcus mutans na saliva - Cristiane Yumi Koga-Ito; Clélia Aparecida de Paiva Martins; Ivan Balducci; Antonio Olavo Cardoso Jorge (Sociedade Brasileira de Pesquisa Odontológica, 2004)
Two-hundred and forty individuals were studied, divided into five groups as follows: caries-free children, children with caries, children with rampant caries, young adults with and without caries. Whole stimulated saliva was collected and all individuals were investigated for DMFT/dmft according to the WHO criteria and the simplified oral hygiene index (OHI-S). Quantitative analysis of the total aerobic flora and mutans streptococci in saliva was performed. Also, the level of salivary anti-S. mutans IgA was determined by ELISA. Children with rampant caries showed the highest OHI-S value. The highest total counts of microorganisms were found in the group of children with caries. No statistically significant differences were observed for salivary flow, OHI-S and microorganism counts between the groups of young adults. No correlation between mutans streptococci counts and anti-Streptococcus mutans IgA levels was observed in the studied groups. A correlation between increased anti-Streptococcus mutans IgA levels and caries-free status was observed among young adults but not among children. Duzentos e quarenta indivíduos divididos em cinco grupos foram estudados: crianças livres de cáries, crianças com cáries, crianças com cáries rampantes, adultos jovens com e sem cáries. Saliva total estimulada foi coletada, e todos os indivíduos foram investigados para CPO-D/ceo-d seguindo-se os critérios da OMS e o índice de higiene oral simplificado (IHOS). Foi também realizada a quantificação da microbiota aeróbica total e de estreptococos do grupo mutans na saliva. Além disso, o nível de IgA anti-S. mutans foi determinado por ELISA. Crianças com cárie rampante apresentaram maior valor de IHOS. A contagem total de microrganismos mais elevada foi encontrada no grupo de crianças com cárie. Nenhuma diferença estatisticamente significativa foi observada em relação a fluxo salivar, IHOS e contagens de microrganismos entre os grupos de adultos jovens. Nenhuma correlação entre contagem de estreptococos do grupo mutans e níveis de IgA anti-Streptococcus mutans foi observada em nenhum dos grupos estudados. Foi encontrada uma correlação entre níveis mais altos de IgA anti-S. mutans e ausência de cáries entre os adultos jovens, mas não entre as crianças.